Analysis of Mathematics Curriculum Ability Development Based on Computer Data Mining - Zhao, FengMing (Journal of physics. Conference series, 2020)
In this paper, the data mining techniques is used to analyze the mathematics curriculum ability development. Firstly, a data warehouse of students' academic achievement is established. The comparative concept description method in data mining techniques is used to analyze various abilities of students of different genders from different majors over the years, and the corresponding reform measures for the teaching contents and approaches are proposed.